KONTRIBUSI HUKUM ISLAM DALAM PROSES TAQNÎN UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN - Abdul Hamid (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
The existence of Islamic Law Banking in Indonesia has been recognized and known from the Banking Law Number 7 of 1992. This continued with the Banking Law Number 10 of 1998 Juncto Number 7 of 1992, and it is finally regulated with the Banking Law Number 21 of 2008 which confirms that Islamic banking is part of the national banking system. This paper will explain the transformation process of Islamic law into Sharia banking rule in Indonesia. As described in some literatures that Shariah Bank is one of the financial Islamic instruments and institutions. So, I can say that the existence of Shariah bank is the representation of the principles of Islamic economics in fiqh muamalah and the implementation of the Islamic economics norms which can help to improve the economic performance in Indonesia.